Healthcare resource utilization and cost in dementia: are there differences between patients screened positive for dementia with and those without a formal diagnosis of dementia in primary care in Germany?‡. (22nd September 2015) - Michalowsky, Bernhard; Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Wucherer, Diana; Hoffmann, Wolfgang; Flessa, Steffen
ABSTRACT: Background: It is well-known that dementia is undiagnosed, resulting in the exclusion of patients without a formal diagnosis of dementia in many studies. Objectives of the present analyses were (1) to determine healthcare resource utilization and (2) costs of patients screened positive for dementia with a formal diagnosis and those without a formal diagnosis of dementia, and (3) to analyze the association between having received a formal dementia diagnosis and healthcare costs. Method: This analysis is based on 240 primary care patients who screened positive for dementia. Within the baseline assessment, individual data about the utilization of healthcare services were assessed. Costs were assessed from the perspective of insurance, solely including direct costs. Associations between dementia diagnosis and costs were evaluated using multiple linear regression models. Results: Patients formally diagnosed with dementia were treated significantly more often by a neurologist, but less often by all other outpatient specialists, and received anti-dementia drugs and day care more often. Diagnosed patients underwent shorter and less frequent planned in-hospital treatments. Dementia diagnosis was significantly associated with higher costs of anti-dementia drug treatment, but significantly associated with less total medical care costs, which valuated to be € 5, 123 compared, to € 5, 565 for undiagnosed patients. We found no association between dementia diagnosis and costs of evidence-based non-medication treatment or total healthcare cost (€ 7, 346 for diagnosed vs. € 6, 838 for undiagnosed patients). Conclusion: There are no significant differences in total healthcare cost between diagnosed and undiagnosed patients. Dementia diagnosis is beneficial for receiving cost-intensive anti-dementia drug treatments, but is currently insufficient to ensure adequate non-medication treatment for community-dwelling patients.